2001
DOI: 10.1017/s1355838201002035
|View full text |Cite
|
Sign up to set email alerts
|

Structural features in the HIV-1 repeat region facilitate strand transfer during reverse transcription

Abstract: Two obligatory DNA strand transfers take place during reverse transcription of a retroviral RNA genome. The first strand transfer is facilitated by terminal repeat (R) elements in the viral genome. This strand-transfer reaction depends on base pairing between the cDNA of the 59R and the 39R. There is accumulating evidence that retroviral R regions contain features other than sequence complementarity that stimulate this critical nucleic acid hybridization step. The R region of the human immunodeficiency virus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
108
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 76 publications
11
108
3
Order By: Relevance
“…Several in vitro works have suggested an implication of hairpin structures in promoting copy choice by bringing donor and acceptor RNAs into close proximity (33,34) or by favoring pausing of reverse transcription at the base of the hairpin followed by strand transfer within the hairpin region (20). Based on an in vitro study of the same C2 sequence studied here, we previously proposed that strand transfer would begin by the docking of the nascent DNA onto the acceptor RNA in the loop of the hairpin and would then proceed through a process of strand exchange similar to branch migration occurring during DNA-DNA recombination (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro works have suggested an implication of hairpin structures in promoting copy choice by bringing donor and acceptor RNAs into close proximity (33,34) or by favoring pausing of reverse transcription at the base of the hairpin followed by strand transfer within the hairpin region (20). Based on an in vitro study of the same C2 sequence studied here, we previously proposed that strand transfer would begin by the docking of the nascent DNA onto the acceptor RNA in the loop of the hairpin and would then proceed through a process of strand exchange similar to branch migration occurring during DNA-DNA recombination (10).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why some retroviruses have evolved a shorter homologous region for ϪsssDNA transfer is not known, but the effects of differences in homology length may be compensated by a myriad of factors. Berkhout et al (24) proposed that in addition to homology, structural features of the HIV-1 repeat regions facilitate minus strand transfer. They propose that "kissing interactions" between the anti-TAR and antipoly(A) hairpins in the ϪsssDNA and the TAR and poly(A) of the 3Ј-untranslated region (acceptor) initiate the first interactions between the cDNA and acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…In murine leukemia virus, an R region with as little as 12 or 14 nt does not affect transfer significantly (21,22). In addition to homology, RNA structure has also been implicated in the minus strand transfer mechanism (17,23,24).The viral NC protein has been shown to stimulate minus strand transfer (see Ref. 1 and references therein and Ref.…”
mentioning
confidence: 99%
“…In parallel, studies carried out on RNA templates containing hairpin regions have suggested that such structures could favor template switching by RTs (13,16,17). In these cases it was proposed that the hairpin structures enhance the probability of strand transfer by mediating an interaction between donor and acceptor RNA that increases their spatial proximity (13,16,17).…”
mentioning
confidence: 99%
“…In parallel, studies carried out on RNA templates containing hairpin regions have suggested that such structures could favor template switching by RTs (13,16,17). In these cases it was proposed that the hairpin structures enhance the probability of strand transfer by mediating an interaction between donor and acceptor RNA that increases their spatial proximity (13,16,17). Extensive random searches for the occurrence of recombination hot spots during in vitro reverse transcription by HIV-1 RT had revealed the correlation between the location of these hot spots and the presence of predicted hairpin regions in the RNA template (14,18).…”
mentioning
confidence: 99%